2014
DOI: 10.1111/ijn.12366
|View full text |Cite
|
Sign up to set email alerts
|

Perceived knowledge, skills, attitude and contextual factors affecting evidence‐based practice among nurse educators, clinical coaches and nurse specialists

Abstract: Evidence-based practice (EBP) in the clinical setting is recognized as an approach that leads to improved patient outcomes. Nurse educators (NEs), clinical coaches (CCs) and nurse specialists are in key positions to promote and facilitate EBP within clinical settings and have opportunities to advance practice. Therefore, it is important to understand their perceptions of factors promoting EBP and perceived barriers in facilitating EBP in clinical settings, before developing educational programmes. This paper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 32 publications
(103 reference statements)
10
72
0
5
Order By: Relevance
“…Mentors relied on national and local guidelines and policies to inform their practice and to provide assurance that it is evidence‐based. These findings are similar to that of Malik et al who found 90% of nurse educators and 94% of clinical nurse specialists used policies and protocols for information and knowledge . A study across 10 acute hospitals also found nurses relied on hospital policies and procedures for knowledge .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Mentors relied on national and local guidelines and policies to inform their practice and to provide assurance that it is evidence‐based. These findings are similar to that of Malik et al who found 90% of nurse educators and 94% of clinical nurse specialists used policies and protocols for information and knowledge . A study across 10 acute hospitals also found nurses relied on hospital policies and procedures for knowledge .…”
Section: Discussionsupporting
confidence: 87%
“…Melnyk et al also reported nurses' negative beliefs towards EBP impacted their intention to implement this approach in their daily practice . Even though, for nurses, EBP is frequently supported by guidelines and policies …”
Section: Introductionmentioning
confidence: 99%
“…The responsibility of providing evidence based practice cannot lie on the shoulders of one qualified nurse, but in a collective group of qualified nurses. Nurses need the professional autonomy and the authority to implement evidence based practice into their practice (Saunders, Stevens, et al., ) and allocated time away from the bedside dedicated to finding and critiquing the literature (Malik, McKenna, & Plummer, ).…”
Section: Resultsmentioning
confidence: 99%
“…Equipping involves ensuring that nurses have access to a computer or other databases to search available literature, evidence based practice mentors, and access to current peer‐reviewed nursing journals at the point of care (Saunders & Vehvilainen‐Julkunen, ; Thiel & Ghosh, ). Lack of resources has been reported in multiple studies as one of the greatest barriers to evidence based practice implementation (Malik et al., ; Melnyk et al., ; Patelarou et al., ; Thorsteinsson & Sveinsdottir, ). In some studies, despite having available evidence based practice resources, some nurses report not knowing what is available or how to access it (Thorsteinsson & Sveinsdottir, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation